-4x + 6y = 12
x + 2y = -10
First solve for x in the second equation
x + 2y = -10
x = -10 - 2y
Now we have a value for x so we can substitute it into the other equation
-4 (-10 - 2y) + 6y = 12
Now solve for y
40 + 8y + 6y = 12
40 + 14y = 12
14y = -28
y = -2
Now we have a value for y that we can plug into one of the original equations so we can solve for x
x + 2y = -10
x + 2(-2) = -10
x - 4 = -10
x = -6
Your solution set is
(-6, -2)
Answer: is this correct
Step-by-step explanation:
Hello to answer your question fully
$1,345 is 500 x 2.69
Signed by, Frequent Answerer Sargedog
I'm in middle school but I don't even know what is thatttttt????
Answer:
i thick it is c so good luck
Step-by-step explanation: